The Impact of Human Resource Development, Work Stress, and Job Promotion on Employee Performance at PT. Bank Sumut Pusat Medan - Fadillah, Beby; Handoko, Bagus; Pentana, Sopi (Journal Boas : Business, Economics, Accounting And Management, 2024)
This study aims to analyze the effect of human resource development, work stress, and job promotion on employee performance at PT. Bank Sumut Pusat Medan. The method used in this study is a quantitative approach with an associative design, which aims to determine the relationship between the independent variable and the dependent variable. The population in this study consisted of 400 employees, and the sample taken was 80 employees. Data were collected through questionnaires and analyzed using SPSS to test reliability and multiple linear regression. The results showed that human resource development had a negative effect on employee performance, while work stress and job promotion had a positive and significant effect on employee performance. These findings provide important insights for management in designing more effective human resource development strategies to improve employee performance.